2009
DOI: 10.4143/crt.2009.41.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Ginsenosides Compound K and Rh2 Enhance Fas-induced Cell Death of Human Astrocytoma Cells Through Distinct Apoptotic Signaling Pathways

Abstract: I n t r o d u c t i o nGlioblastoma multiforme (GBM) is the most malignant and common brain tumor and it comprises ~23% of all primary brain tumors in adults. These malignancies are refractory to all the current therapeutic approaches, including surgery, radiotherapy and chemotherapy. Fas (CD95 or APO-1) is a member of the TNF/NGF receptor family, and Fas induces caspase-dependent apoptotic death in various transformed cells (1,2). Fas ligation with natural ligand or agonistic anti-Fas antibody is followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…*Pp0.01 compared with TRAIL-alone treated samples act as anti-apoptotic mediators. 13,37 We further confirmed that PKCd is also involved in FasL-mediated signaling (Supplementary Figure 7). Reactive oxygen species, particularly H 2 O 2 , have been recognized as second messengers in receptor-mediated signaling processes including proliferation, inflammation, and apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…*Pp0.01 compared with TRAIL-alone treated samples act as anti-apoptotic mediators. 13,37 We further confirmed that PKCd is also involved in FasL-mediated signaling (Supplementary Figure 7). Reactive oxygen species, particularly H 2 O 2 , have been recognized as second messengers in receptor-mediated signaling processes including proliferation, inflammation, and apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…CK is rapidly absorbed in the gastrointestinal tract and is retained for a long time in rat plasma [20,21]. The anti-angiogenic effect of CK was also reported [14,16,22]. Although the anti-cancer effects of ginsenosides have been studied extensively in other cancer models, the effect of ginsenosides on NPC is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the deglycosylated forms often show better pharmacological activity in the body than the glycosylated forms (17,21). For example, the ginsenosides compound K (CK) and Rh2, which are widely known as inducers of tumor cell apoptosis (10,18), are deglycosylated into PPD. Compared to Rh2, PPD shows better pharmacological effects on B16 melanoma cells (28).…”
mentioning
confidence: 99%